Higher education funding in Brazil and the income contingent loans alternative - Andrade, Bruna Costa Cataldo de (2024)
The current economic and political crises in Brazil have been raising debates about the future of higher education funding, which has three main pillars: full government funding, full private funding, and mixed funding. The first corresponds to tax-financed public institutions. For those who cannot access the public system or afford full costs of the private, the government offers two programs: PROUNI and FIES. We critically analyze these three public policies and one of the main alternatives in literature, the Income Contingent Loan (ICL). The general objective is to analyze public policies for higher education funding in Brazil and ICL as alternative. We aim to map and characterize the system, not to discuss each policy in depth. We present their structures so problems can be identified and solutions can be researched with a comprehensive understanding of the system. The specific objectives are making a literature review of the ICL approach; describing higher education funding in Brazil; and discussing what benefits/difficulties implementing an ICL can bring. The objectives are guided by the research question: “What are the characteristics and challenges of funding higher education in Brazil, and what contributions the ICL perspective can give to solve the latter?”. Conclusions indicate the ICL literature positively contributes to the identification of the challenges but particularities of the country must be taken into consideration. Also, there is mixed-evidence concerning the implementation of a nation-wide ICL, but a strong recommendation for making FIES one – with attempts already in development. Lastly, blind-alleys were identified in the debate, leading to reform propositions disconnected from the country’s challenges.